'I had to pop a wheelie and pay extra attention in order not to fall:' embodied experiences of two wheelchair tennis athletes transgressing ableist and gendered norms in disability sport and university spaces. Issue 3 (4th May 2021) - Lynch, Shrehan; Hill, Joanne
ABSTRACT: When bodies move in certain contexts, it can mean very different things for different people. In our society, some bodies are more valued than others, and detrimentally, this can mean that certain types of bodies are ostracised and segregated to the outskirts of production economies and society. Dis/ability sport spaces, able-bodied sports spaces and able-bodied university spaces have been an under-researched area when considering how the body moves throughout these spaces for elite wheelchair athletes taking part in university courses. To learn more, this paper drew on feminist poststructuralism and new materialist perspectives and shared an insight into how two athletes with dis/abilities transgressed abled and gendered norms in different spaces and how they positioned themselves as athletic bodies and disabled bodies in these spaces. Employing a post-critical ethnographic design, we found that dependent on the space a dis/abled body is in constant flux as to when it feels marginalised and different (typically able-bodied spaces) and when it feels included, valued, and strong (typically dis/abled spaces). Significantly, the materiality of the institutional structures of universities, founded upon historic aesthetics of beauty dictated the physical spaces the athletes entered and created spaces of exclusion based on capitalist and ableist ideologies.